Consumers’ Intentıon To Use “Buy Now Pay Later” In Malaysıa. - Lee Hoei Min; Tai Lit Cheng (Universitas Internasional Batam, 2023)
Buy Now Pay Later demand is increasing due to the technology advantage which is easier to register than the credit cards. It provides a payment solution which allowing consumers to buy goods or services immediately by delaying payment with zero per cent interest. However, in Malaysia, Buy Now Pay Later is still at its infant stage. Given the importance of this payment method, marketers should understand how this payment method able to expand in Malaysia. This research investigated the Malaysian consumers intention on what effects them in using Buy Now Pay Later. This study uses a non probability sampling method of 200 respondents using SPSS version 27. Results showed that performance expectancy, facilitating conditions, and perceived security affect consumers intention to use Buy Now Pay Later whereas social influence and effort expectancy do not have direct effect. Thus, it is suggested Paylater providers should always improve their performance such as reduce downtime and concentrate on gaining their customers' trust in terms of security. This study seeks to assist paylater providers in the development of effective marketing strategies for further increase usage of this paylater function. Besides, it can alert paylater users on the risk on potential security threats and impulse purchase when using Paylater. Understanding the significance of the additional factor such as perceived security, may provide a reference for the future revision of UTAUT. This study consisted a few limitations such as unevenly distributed respondents' income as most respondents are B40. This is due to some of the M40 and T40 respondents are not interested in filling out the questionnaire as they think it is time-consuming. Moreover, M40 and T40 respondents are difficult to reach. Then, there is limited variables being researched due some respondents stated variables such as brand image or advertisement are playing important role. Thus, it is recommended that surveys be filled equally to each income category to improve data gathering consistency and accuracy while other variables should be added in a future research.